Effect of Biogas Poultry Manure on Soil Fertility in Cereal-Legume based Cropping System - Shanti, M.; Naaiik, R. V. T. Balazzii; Devi, K. B. Suneeta; Shashikala, T.; Reddy, J. Rajasekhar; Chiranjeevi, Ch. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during kharif and rabi, 2006-08 at All India Coordinated Research Project on Forage Crops, Livestock Research Institute, Rajendranagar, Hyderabad to study the effect of biogas poultry manure (BPM) on soil fertility in cereal-legume based cropping system. Application of 50, 75 and 100% N through biogas poultry manure (BPM) and poultry manure resulted in a significant increase in cob and Stover yield of maize. The highest cob yields were recorded in the treatment where 100% of N was substituted by BPM, recording 55.6 q ha-1 of cob yields and was significantly superior to all other treatments. Better yields in biogas poultry manure compared to that of poultry manure could be due to the fact that biogas poultry manure contains all the nutrients in more mineralized form compared to that of poultry manure as it had already passed through a part of decomposition in the biogas unit. The C:N ration of BPM is less than that of PM. The green fodder yields of cowpea which was grown on residual fertility were significantly influenced by poultry manure and biogas poultry manure. The soil fertility status of available major nutrients (N, P2O5 and K2O) was found to be significantly higher in the treatments that received N through biogas poultry manure or poultry manure. The highest buildup of available nitrogen in poultry manure treated plots might be due to less mineralization during crop growth period resulting in more accumulation in soil. Effect on the soil physico-chemical properties was non-significant.